The role of right precordial intrinsicoid deflection time in determining the conversion of Type 2 Brugada ECG pattern to Type 1 Brugada ECG pattern on 12-lead electrocardiogram with ajmaline test (Annals of Medical Research, 2021)
Aim: Brugada syndrome is a genetic disorder associated with fatal ventricular arrhythmias. Type 1 (cove-type) ECG pattern is diagnostic for Brugada syndrome while Type 2 (saddle-type) ECG pattern requires ajmaline test to convert it to Type 1 ECG pattern to make the diagnosis. However, this test may cause ventricular arrhythmias and death. Intrinsicoid deflection time (IDT) is an ECG parameter reflecting intraventricular conduction delay, which is one of the pathophysiological mechanisms for Brugada syndrome. We examined IDT for conversion of type 2 Brugada pattern to type 1 Brugada pattern in ajmaline test.Materials and Methods: This retrospective study involved patients with Type 2 ECG pattern that was converted to Type 1 ECG pattern with ajmaline test (Group 1) and an age- and sex-matched control group with a normal ECG (Group 2). IDT was digitally measured in the lead V2, from the onset of the QRS complex to the peak of the R wave and compared between the study groups. A ROC curve was drawn to test the predictive ability of IDT for conversion to Type 1 ECG pattern. Results: There were 28 subjects (21 men, 7 women) in Group 1 and 28 subjects (21 men, 7 women) in Group 2. Group 1 had a significantly greater IDT than Group 2 (28 (17.1-78.0) msec vs 21 (16.0-36.9) msec; p0.05). In ROC analysis, IDT significantly predicted conversion to Type 1 ECG pattern, and a cut-off value of 25 msec for IDT had a sensitivity of 55.6% and a specificity of 81.5% for predicting conversion to Type 1 ECG pattern. Conclusion: IDT was significantly longer in patients with Type 2 ECG pattern converted to Type 1 ECG pattern by ajmaline compared with the control subjects. IDT has a good specificity and a modest sensitivity for prediction of conversion to Type 1 ECG pattern.
Keywords: Brugada syndrome; ajmaline test; intrinsicoid deflection time